A satellite study of intensities of cyclonic storms in the Bay of Bengal (MAUSAM, 1975)
Seven sequences of satellite picture of severe cyclonic stores, which developed in the Bay of Bengal have been examined and day to day changes m their intensities have been discussed With reference to the application of Dvorak's technique for the analysis and forecasting of tropical cyclone intensities. Salient features of storm development in Bay of Bengal, as observed in the satellite pictures, have been highlighted. A comparison of this technique has also been II1ade with synoptic inferences.